2006
DOI: 10.1016/j.ijantimicag.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of sigB and sarA to distinct multiple antimicrobial resistance mechanisms of Staphylococcus aureus

Abstract: Multiple antimicrobial resistance in Staphylococcus aureus can result from mutations leading to reduced susceptibility to Pine oil-based cleaners (PS(RS)) as well as following growth with the non-steroidal anti-inflammatory salicylate. We now define the contributions of the alternative sigma factor (sigB) and staphylococcal accessory regulator (sarA) to these mechanisms. We conclude that sarA plays a more prominent role than sigB in overall intrinsic multiple antimicrobial resistance. Both genes have similar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…This suggests that sarA is upregulated by salicylate induction, which was demonstrated by real-time PCR analysis in our previous study using SH1000 (46). We also demonstrated that sarA is required for the full expression of intrinsic multiple antimicrobial resistance (36) and salicylate-induced reduced susceptibility to multiple anti- a Cip, ciprofloxacin; Sal, 2 mM salicylate; Fus, fusidic acid; PS, Pine-Sol; FI, increase (n-fold) in resistance expression of mgr::cat mutant compared to parent or salicylate-induced increase in resistance level compared to uninduced; FD, salicylate-induced decrease (n-fold) in resistance level compared to uninduced, or decrease in resistance expression of mgr::cat mutant compared to parent; ND, not determined.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…This suggests that sarA is upregulated by salicylate induction, which was demonstrated by real-time PCR analysis in our previous study using SH1000 (46). We also demonstrated that sarA is required for the full expression of intrinsic multiple antimicrobial resistance (36) and salicylate-induced reduced susceptibility to multiple anti- a Cip, ciprofloxacin; Sal, 2 mM salicylate; Fus, fusidic acid; PS, Pine-Sol; FI, increase (n-fold) in resistance expression of mgr::cat mutant compared to parent or salicylate-induced increase in resistance level compared to uninduced; FD, salicylate-induced decrease (n-fold) in resistance level compared to uninduced, or decrease in resistance expression of mgr::cat mutant compared to parent; ND, not determined.…”
Section: Resultssupporting
confidence: 65%
“…It is therefore of interest that the overexpression of norB leads to increased ethidium resistance (52) and that growth in the presence of salicylate induces ethidium efflux and resistance (43). Since growth of S. aureus in the presence of salicylate reduces susceptibility to fusidic acid (42) and common house cleaners (46) and reduces mgrA expression (this study), we hypothesized that mgrA mutants should demonstrate reduced susceptibility to fusidic acid and a common house cleaner. mgrA::cat mutants of strains Becker (CYL1040) and Newman (CYL1050) demonstrated reduced susceptibility to ciprofloxacin, as expected (53), and to a common house cleaner but increased susceptibility to fusidic acid (Table 4).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations